METODE CARD SORT UNTUK MENINGKATKAN PENGUASAAN KOSA KATA DALAM PEMBELAJARAN BAHASA ARAB DI SEKOLAH - Hestiyani, Yosha (Departemen Pendidikan Bahasa Arab, 2019)
This study intends to improve vocabulary mastery through learning Arabic in schools using the card sort method in class X students at SMK Yapari-Aktripa Bandung. This research focuses on the card sort method which is expected to improve Arabic vocabulary mastery. The purpose of this study was to determine significant differences regarding the ability to master Arabic vocabulary before and after treatment using the card sort method. The results of this study indicate that the average pretest value of the experimental class and the control class there is no significant difference or have the same ability that is 57.09 and 58.04. While the posttest scores of the experimental class and the control class there are significant differences, namely 90.04 and 77.90. Based on the n-Gain of the experimental class 76.41% and the control class of 45.66%, the n-Gain of the experimental class is greater than the control class. So it can be concluded that the card sort method is an effective method to improve the mastery of Arabic vocabulary.